TRADE AND ECONOMIC RELATIONS OF TURKESTAN REGION WITH CHINA IN THE SECOND HALF OF THE XIX - BEGINNING OF THE XX CENTURY (on the example of Fergana region) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the trade policy of Russia with Kashgar (East Turkestan) through Central Asia in the second half of the 19th and early 20th centuries. Fergana region (Kokand) has become one of the main transfer points in Russian-Kashgar trade relations. After the conquest of the region by the Russian Empire, the colonial rulers sought to benefit from the development of trade both in local markets and in the territories adjacent to Turkestan's external borders, using the capital of foreign and local entrepreneurs. The export of raw materials and the import of finished products were established.